A two-sample Mendelian randomization study of type 1 diabetes and the risk of 22 site-specific cancers - Mikiyas Amare Getu; Xianbin Zhang; Ying Ying; Peng Gong (Scientific Reports)
Abstract Previous observational studies have suggested a potential link between Type 1 Diabetes (T1D) and site-specific cancer risk. However, the nature of this association remains uncertain due to confounding factors, reverse causation, and biases inherent in observational research. To address this gap, we conducted a two-sample Mendelian randomization (MR) study to assess the causal relationship between T1D and 22 site-specific cancers. Using summary statistics from large-scale genome-wide association studies of European ancestry, comprising data on T1D (N = 520,580) and the 22 site-specific cancers, we selected single nucleotide polymorphisms strongly associated with T1D as instruments for our analysis. Causal relationships were primarily evaluated through inverse-variance weighting-based analyses, supplemented by three additional methods: MR-Egger, weighted median, and mode-based estimate. Sensitivity analyses were performed, excluding genetic variants with potential pleiotropic effects. The finding demonstrated a causal association between T1D and increased risks of lung cancer (OR = 1.018, 95% CI 1.004–1.033, p = 0.011), colorectal cancer (OR = 1.022, 95% CI 1.003–1.041, p = 0.019), and prostate cancer (OR = 1.018, 95% CI 1.005–1.030, p = 0.006). Conversely, T1D was associated with decreased risks of breast cancer (OR = 0.989, 95% CI 0.981–0.998, p = 0.016), lymphoma (OR = 0.999, 95% CI 0.974–0.999, p = 0.003), malignant melanoma (OR = 0.999, 95% CI 0.989–0.999, p = 0.001), and non-melanoma skin cancer (OR = 0.999, 95% CI 0.899–0.999, p = 0.003). Our MR study provides an evidence of causal association between T1D and altered risks of various site-specific cancers. Further research is recommended to validate this finding in diverse populations to enhance the generalizability of findings across different ethnic groups.